2012
DOI: 10.1371/journal.pone.0049392
|View full text |Cite
|
Sign up to set email alerts
|

Working Memory-Related Functional Brain Patterns in Never Medicated Children with ADHD

Abstract: Attention Deficit/Hyperactivity Disorder (ADHD) is a pervasive neurodevelopmental disorder characterized by 3 clusters of age-inappropriate cardinal symptoms: inattention, hyperactivity and impulsivity. These clinical/behavioural symptoms are assumed to result from disturbances within brain systems supporting executive functions including working memory (WM), which refers to the ability to transiently store and flexibly manipulate task-relevant information. Ongoing or past medications, co-morbidity and differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
45
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 51 publications
8
45
0
Order By: Relevance
“…Among the neurodevelopmental disorders with established links to cerebellar dysfunction, executive function deficits are most characteristic of ADHD. A recent study indicated that ADHD participants with impaired working memory show hypoactivation in the anterior cerebellum [56] and that bilateral regions of Crus I were hypoactive in ADHD participants during a working memory paradigm [57]. Gray matter reductions have been reported in multiple cerebellar regions in ADHD [35], including those that are associated with dorsal and ventral attention networks, and reduced functional connectivity has been found in cerebellar regions involved in fronto-parietal networks in children with ADHD [58].…”
Section: Structure–function Relationships: Cognitive Performancementioning
confidence: 99%
“…Among the neurodevelopmental disorders with established links to cerebellar dysfunction, executive function deficits are most characteristic of ADHD. A recent study indicated that ADHD participants with impaired working memory show hypoactivation in the anterior cerebellum [56] and that bilateral regions of Crus I were hypoactive in ADHD participants during a working memory paradigm [57]. Gray matter reductions have been reported in multiple cerebellar regions in ADHD [35], including those that are associated with dorsal and ventral attention networks, and reduced functional connectivity has been found in cerebellar regions involved in fronto-parietal networks in children with ADHD [58].…”
Section: Structure–function Relationships: Cognitive Performancementioning
confidence: 99%
“…In functional studies, these anomalies have been associated with inhibitory and working memory failures and attentional lapses (Q. Cao et al, 2013;Massat et al, 2012). Simply put, the auditory versus visual dichotomy initially proposed when neuropsychology was in its infancy is false, incomplete, and potentially diagnostically misleading.…”
Section: Integrating Network Auditory-visual Interactions and Actimentioning
confidence: 99%
“…We first compared ADHD to non-ADHD controls to localize any brain function deficits. Consistent with previous non-ADHD fMRI studies (Hempel et al, 2004; Jolles et al, 2010; Olesen et al, 2004), we predicted WM training would increase and possibly normalize ADHD WM task-related activation in some or most of these WM circuit regions, particularly left caudal superior frontal sulcus (SFS) and left inferior frontal sulcus (SFS) regions which most consistently show hypofunction in ADHD fMRI studies of short term WM storage (Fassbender et al, 2011; Hale et al, 2007; Prehn-Kristensen et al, 2011; Sheridan et al, 2007; Vance et al, 2007; Wolf et al, 2009) or WM updating (i.e., N-back tasks) (Bayerl et al, 2010; Cubillo et al, 2014; Ko et al, 2013; Kobel et al, 2009; Malisza et al, 2012; Massat et al, 2012; Passarotti et al, 2010; Valera et al, 2005). We also asked whether WM training preferentially altered ADHD brain function engaged during encoding, maintenance, or retrieval of information from WM and examined training effects on WM task difficulty.…”
Section: Introductionmentioning
confidence: 99%